1989
DOI: 10.4319/lo.1989.34.4.0734
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen uptake kinetics in the benthic boundary layer

Abstract: A simple, one-dimensional, transport-reaction model of oxygen uptake by sediments during incubation experiments assumes zero-order reaction kinetics for oxygen removal in the pore water of sediments and takes the apparent diffusive limitation posed by the benthic boundary layer into account. Model calculations are in excellent agreement with experimental data obtained during in situ benthic flux chamber experiments in Gullmarsfjorden, Sweden, during fall (water temp, 10°C) and winter (-1'C). The boundary layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
82
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(93 citation statements)
references
References 38 publications
9
82
2
Order By: Relevance
“…However, it tends to be reduced and released to the overlying water on the sediment or the interstitial water of the sediment as manganese ion by the bacterial activity in the sediment particularly during the warm seasons when bacterial activity is accelerated (Hunt & Kelly 1988). In hypoxic water, manganese ion tends to be released intensively from the sediment (Hall et al 1989, Gerringa 1991, Baden et al 1994. Manganese is harmless in manganese dioxide, whereas manganese ion or its organically bound form is more bioavailable and excessive concentrations are neurotoxic to gastropods (Chemeris et al 1982) and to clams (Beirao 1989).…”
Section: Causes Of Disappearance Of the Macro-benthic Communities On mentioning
confidence: 99%
“…However, it tends to be reduced and released to the overlying water on the sediment or the interstitial water of the sediment as manganese ion by the bacterial activity in the sediment particularly during the warm seasons when bacterial activity is accelerated (Hunt & Kelly 1988). In hypoxic water, manganese ion tends to be released intensively from the sediment (Hall et al 1989, Gerringa 1991, Baden et al 1994. Manganese is harmless in manganese dioxide, whereas manganese ion or its organically bound form is more bioavailable and excessive concentrations are neurotoxic to gastropods (Chemeris et al 1982) and to clams (Beirao 1989).…”
Section: Causes Of Disappearance Of the Macro-benthic Communities On mentioning
confidence: 99%
“…Incubations were stopped when oxygen levels had decreased by more than 20 % to avoid hypoxic conditions and biogeochemical transformations. Hall et al (1989) demonstrated the importance of maintaining the O 2 supply to obtain consistent and relevant data during core incubations.…”
Section: Benthic Oxygen Flux and Nutrient Remineralisationmentioning
confidence: 99%
“…Enhanced diffusive transport, due to the mixing of pore waters by small organisms (meiofauna and microzoobenthos), has been proposed (Archer and Devol, 1992;Meile et al, 2001; to explain discrepancies between SOD estimates derived from in-situ benthic chamber measurements (e.g. Hall et al, 1989) /lmol cm-2 y{l, usually in shallower coastal settings), molecular diffusion underestimates the oxygen fluxes (Jahnke, 2001;. Our modeling results largely agree with this observation, as the sediment DO profiles in a region with low SOD (i.e., the GSL) are reproduced very well by our simple diagenetic model (Fig.…”
Section: Sediment Oxygen Demandmentioning
confidence: 99%